Follow Your Nose: A Key Clue to Understanding and Treating COVID-19 - Edwards, Christopher; Klekot, Oleksandra; Halugan, Larisa; Korchev, Yuri (Frontiers in Endocrinology, 2021)
This paper suggests that ATP release induced by the SARS-CoV-2 virus plays a key role in the genesis of the major symptoms and complications of COVID-19. Infection of specific cells which contain the ACE2 receptor results in a loss of protection of the Mineralocorticoid Receptor (MR). Local activation by cortisol stimulates the release of ATP initially into the basolateral compartment and then by lysosomal exocytosis from the cell surface. This then acts on adjacent cells. In the nose ATP acts as a nociceptive stimulus which results in anosmia. It is suggested that a similar paracrine mechanism is responsible for the loss of taste. In the lung ATP release from type 2 alveolar cells produces the non-productive cough by acting on purinergic receptors on adjacent neuroepithelial cells and activating, via the vagus, the cough reflex. Normal endothelial cells in contrast to the normal aldosterone-selective epithelial cells have very low ACE2 levels and are resistant to infection with the virus, most likely explaining why the young usually only get mild COVID-19 disease. However, shear stress in 3D models of blood vessels with vascular disease where the basement membrane is fibronectin and not collagen induces the expression of ACE2 and hence could explain the susceptibility of particular sub-groups of patients to the severe complications of COVID-19. These relate to the exocytosis of Weibel-Palade bodies from the infected endothelial cells. These contain the Von Willebrand Factor responsible for micro-clotting and angiopoietin-2 which increases vascular permeability and plays a key role in the Acute Respiratory Distress Syndrome. To test this hypothesis this paper reports proof of concept studies in which Mineralocorticoid Receptor blockade using cortisol suppression with low dose dexamethasone and spironolactone has been given to both mild COVID-19 disease and COVID-19 patients with moderate to severe respiratory failure. In the latter group this has been compared with conventional treatment with high dose dexamethasone. The very positive results suggest that blockade of the Mineralocorticoid receptor and hence of ATP and, possibly, viral release, can produce major benefit.